Angiofollicular and plasmacytic polyadenopathy: a pseudotumourous syndrome with dysimmunity. Issue 11 (November 1980) - Diebold, J; Tulliez, M; Bernadou, A; Audouin, J; Tricot, G; Reynes, M; Bilski-Pasquier, G
Abstract : Two cases are reported of an apparently distinct type of immune disorder. Beginning with mild anaemia and widespread massive lymphadenopathy, the disease progressed to a fatal autoimmune type haemolytic anaemia. Serum investigation showed polyclonal hypergamma-globulinaemia and some autoantibodies. Repeat lymph node biopsies in each case showed hyperplasia within B lymphocyte territory (follicular hyperplasia and polyclonal plasmacytosis with IgG predominance) and atrophy of T dependent areas. Dilatation of lymph sinuses, vascular proliferation, and sclerosis were striking features. This appears to be a new entity, and reasons are given for separating this disease from other pseudotumourous lymph node disorders associated with dysimmunity.